2017
DOI: 10.1177/0363546517719460
|View full text |Cite
|
Sign up to set email alerts
|

Cam Deformities and Limited Hip Range of Motion Are Associated With Early Osteoarthritic Changes in Adolescent Athletes: A Prospective Matched Cohort Study

Abstract: At 5 years, young athletes with LROM of the hip showed increased progressive degenerative changes on MRI and radiographs compared with matched controls. Although the majority of these participants remained asymptomatic, those with features of FAI had radiographic findings consistent with early osteoarthritis. These outcomes suggest that more aggressive screening and counseling of young active patients may be helpful to prevent hip osteoarthritis in those with FAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 57 publications
1
62
0
1
Order By: Relevance
“…Experimentally inducing a cam lesion in sheep has demonstrated significant damage and degenerative changes of the cartilage and labrum at the corresponding location within the acetabulum in vivo. The relationship between cam location and the location of chondrolabral damage was also reported in humans, and is thought to be causal in the development of osteoarthritis . This reproducible model therefore provides an experimental platform, which has the potential to answer clinically relevant questions in the context of FAI.…”
Section: Discussionmentioning
confidence: 62%
“…Experimentally inducing a cam lesion in sheep has demonstrated significant damage and degenerative changes of the cartilage and labrum at the corresponding location within the acetabulum in vivo. The relationship between cam location and the location of chondrolabral damage was also reported in humans, and is thought to be causal in the development of osteoarthritis . This reproducible model therefore provides an experimental platform, which has the potential to answer clinically relevant questions in the context of FAI.…”
Section: Discussionmentioning
confidence: 62%
“…The combination of severe cam‐type deformity and decreased internal rotation (less than 20°) at baseline resulted in an even more pronounced adjusted OR of 25.2, and in a positive predictive value of 52.6% for developing end‐stage OA. The work of Reichenbach et al, Wyles et al, and Peters et al, have also showed the higher prevalence of cam morphology among males with the associated limited internal rotation.…”
Section: Discussionmentioning
confidence: 90%
“…Studying a large cohort of individuals (700) who underwent primary total hip arthroplasty before the age of fifty, Clohisy et al found that over 60% of the hips had radiographic evidence of cam‐type femoroacetabular impingement ( strength ). The 20‐year risk of developing OA or needing THA in a hip of Tönnis 0 with cam morphology after a contralateral THA was 22%; compared to a 14% in hips with normal morphology . In a more recent large longitudinal multi‐centre cohort of over thousand individuals (the CHECK cohort), it was found that a moderate (α angle >60°) and severe (α angle >83°) cam‐type deformity resulted in adjusted odds ratio (OR) of 3.67 (95%CI 1.68–8.01) and 9.66 (95%CI 4.72–19.78), respectively, for developing end‐stage OA .…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence is high among athletes and intense physical activity during adolescence is believed to be a risk factor for development of hip morphologic abnormalities. A recent observational study followed adolescent athletes with limited range of motion of the hip joint, a finding commonly associated with FAI 38 . Athletes with limited hip range of motion showed increased progressive degenerative changes on MRI at 5 years.…”
Section: Prediction Prognostic and Progression Studiesmentioning
confidence: 99%